2013
DOI: 10.1098/rsbl.2013.0051
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent functional divergence of early tetrapod keratins in amphibian toe pads and mammalian hair

Abstract: Amphibians have invaded arboreal habitats multiple times independently during their evolution. Adaptation to these habitats was nearly always accompanied by the presence or appearance of toe pads, flattened enlargements on tips of fingers and toes that provide adhesive power in these environments. The strength and elasticity of the toe pad relies on polygonal arrayed cells ending in nanoscale projections, which are densely packed with cytoskeletal proteins. Here, we characterized and determined the evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…4). In line with results of previous studies 27,28 , we identified Krt24 -like genes but not 1:1 orthologs of Krt24 besides Krt222 in fish and amphibians. In the alligator a Krt24 -like gene is located between Krt222 and Krt10 , and three Krt24 -like genes are present in the platypus, representing basal mammals (Supplementary Tables S1–S7; Suppl.…”
Section: Resultssupporting
confidence: 92%
“…4). In line with results of previous studies 27,28 , we identified Krt24 -like genes but not 1:1 orthologs of Krt24 besides Krt222 in fish and amphibians. In the alligator a Krt24 -like gene is located between Krt222 and Krt10 , and three Krt24 -like genes are present in the platypus, representing basal mammals (Supplementary Tables S1–S7; Suppl.…”
Section: Resultssupporting
confidence: 92%
“…4 B and C ). Of note, the last two exons of the keratin genes most closely related to KRT10 , that is, KRT12 and KRT24 – KRT28 (Vandebergh and Bossuyt 2012; Vandebergh et al. 2013), are spliced in phase 1, like KRT10x1 .…”
Section: Resultsmentioning
confidence: 99%
“…2018). Together with comparative studies of keratins in phylogenetically diverse vertebrates (Zimek and Weber 2005; Vandebergh and Bossuyt 2012; Vandebergh et al 2013; Greenwold et al. 2014; Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…the toe pads in frogs and hairs in mammals (Vandebergh et al . ). The Upper Permian coprolitic findings from South Africa and Russia (described herein) possibly provide the first direct evidence of pre‐Mesozoic hairs of non‐mammalian origin.…”
Section: Discussionmentioning
confidence: 97%